Perbandingan Politik dan Pendidikan Islam dalam Meningkatkan Sdm di Era Rasullah dengan Era Modern dan Digitalisasi - Muhamad Nur Abu Hurairah; Jamrizal; Salahudin (Darajat: Jurnal Pendidikan Agama Islam, 2026)
This study aims to examine the comparison between Islamic politics and education during the era of the Prophet Muhammad (peace be upon him) and the modern/digital era in an effort to improve the quality of human resources. The research employs a qualitative approach using library research by reviewing various relevant literature, journals, and academic sources. The findings indicate that during the Prophet’s era, Islamic education emphasized the development of faith, morals, and character through direct exemplification based on divine revelation, which successfully produced human resources balanced in faith, knowledge, and practice. Meanwhile, in the modern/digital era, Islamic education has undergone significant development through the utilization of technology, which facilitates access to information, enhances learning flexibility, and develops intellectual abilities and skills. However, these advancements are also accompanied by various challenges, such as moral decline, a crisis of character, and the less optimal internalization of Islamic values. Therefore, this study highlights the importance of developing an integrative model of Islamic education by combining the spiritual strengths inherited from the Prophet’s era with technological advancements in the digital age. Through this approach, it is expected to produce human resources who are not only intellectually competent but also possess strong character grounded in Islamic values.